2005
DOI: 10.1287/mnsc.1040.0341
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Options, Supply Contracting, and Electronic Markets

Abstract: T his paper develops a framework for analyzing business-to-business (B2B) transactions and supply chain management based on integrating contract procurement markets with spot markets using capacity options and forwards. The framework is motivated by the emergence of B2B exchanges in several industrial sectors to facilitate such integrated contract and spot procurement. In the framework developed, a buyer and multiple sellers may either contract for delivery in advance (the "contracting" option) or they may buy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
111
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 205 publications
(119 citation statements)
references
References 26 publications
2
111
0
Order By: Relevance
“…Detailed literature reviews can be found in Wu and Kleindorfer (2005) and Martínez-de-Albéniz and Simchi-Levi (2005). Recently, several papers have incorporated spot market and capacity limits into supply option models.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed literature reviews can be found in Wu and Kleindorfer (2005) and Martínez-de-Albéniz and Simchi-Levi (2005). Recently, several papers have incorporated spot market and capacity limits into supply option models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The combination of spot purchases and supply options has seen widespread applications in capitalintensive industries, such as commodity chemicals, electric power, and semiconductors (Kleindorfer andWu 2003, Wu andKleindorfer 2005). The challenge of such hybrid commodity procurement is exacerbated if there are further restrictions that require buying firms to reserve capacity in blocks.…”
Section: Introductionmentioning
confidence: 99%
“…Xing, Wang and Feng [6] from the supply chain and logistics point of view of B2B electronic trading market research. At the beginning of the study, scholars began to study the B2B electronic trading market mainly from how to reduce the transaction cost and how to influence the transaction mode.…”
Section: Literature Reviewmentioning
confidence: 99%
“…B2B electronic trading market in the trading model there are two, one option trading, and the second is the spot transactions [5][6][7][8]. Their study show that the spot market is mobile, they are the market liquidity is defined as: traders intend to buy and sell, according to the then market price can only be a certain probability to find the right transaction Object, this article also uses this definition.…”
Section: Description Of the Problemmentioning
confidence: 99%
“…Yi & Scheller-Wolf (2003) studied the nature of the optimal inventory policy when such a dual sourcing is used, in the presence of a fixed cost for the spot market participation. Wu & Kleindorfer (2005) proposed a general framework with integrated long-term and short-term contract decisions for non-storable commodities. Kouvelis et al (2013) studied the problem of dual sourcing with financial hedging for storable commodities.…”
Section: Dual Sourcing In Supply Chain Managementmentioning
confidence: 99%